Gaseous hydrogen sulfide protects against myocardial ischemia-reperfusion injury in mice partially independent from hypometabolism. - Pauline M Snijder; Rudolf A de Boer; Eelke M Bos; Joost C van den Born; Willem-Peter T Ruifrok; Inge Vreeswijk-Baudoin; Marcory C R F van Dijk; Jan-Luuk Hillebrands; Henri G D Leuvenink; Harry van Goor (PLoS ONE, 2013)
BACKGROUND: Ischemia-reperfusion injury (IRI) is a major cause of cardiac damage following various pathological processes. Gaseous hydrogen sulfide (H2S) is protective during IRI by inducing a hypometabolic state in mice which is associated with anti-apoptotic, anti-inflammatory and antioxidant properties. We investigated whether gaseous H2S administration is protective in cardiac IRI and whether non-hypometabolic concentrations of H2S have similar protective properties. METHODS: Male C57BL/6 mice received a 0, 10, or 100 ppm H2S-N2 mixture starting 30 minutes prior to ischemia until 5 minutes pre-reperfusion. IRI was inflicted by temporary ligation of the left coronary artery for 30 minutes. High-resolution respirometry equipment was used to assess CO2-production and blood pressure was measured using internal transmitters. The effects of H2S were assessed by histological and molecular analysis. RESULTS: Treatment with 100 ppm H2S decreased CO2-production by 72%, blood pressure by 14% and heart rate by 25%, while treatment with 10 ppm H2S had no effects. At day 1 of reperfusion 10 ppm H2S showed no effect on necrosis, while treatment with 100 ppm H2S reduced necrosis by 62% (p<0.05). Seven days post-reperfusion, both 10 ppm (p<0.01) and 100 ppm (p<0.05) H2S showed a reduction in fibrosis compared to IRI animals. Both 10 ppm and 100 ppm H2S reduced granulocyte-influx by 43% (p<0.05) and 60% (p<0.001), respectively. At 7 days post-reperfusion both 10 and 100 ppm H2S reduced expression of fibronectin by 63% (p<0.05) and 67% (p<0.01) and ANP by 84% and 63% (p<0.05), respectively. CONCLUSIONS: Gaseous administration of H2S is protective when administered during a cardiac ischemic insult. Although hypometabolism is restricted to small animals, we now showed that low non-hypometabolic concentrations of H2S also have protective properties in IRI. Since IRI is a frequent cause of myocardial damage during percutaneous coronary intervention and cardiac transplantation, H2S treatment might lead to novel therapeutical modalities.